Effectiveness of Read-Answer-Discuss-Explain-Create Learning Model in Improving Creative Problem Solving Ability of Elementary School Students - Nurhalimah, Siti; Mudopar, Mudopar; Setiawan, Dadan; Panehafo, Elina Amadhila (Universitas Pendidikan Indonesia, 2025)
This study investigated the alignment of the RADEC model with psychological principles and cognitive processes to strengthen creative thinking skills. The method used in this study was quasi-experiment with non-equivalent pretest posttest control group design. A total of 48 students as samples of this study were grouped into experimental groups and control groups. The data were collected through test instruments in the form of case study questions to assess students' creative thinking skills. The data were analyzed through descriptive statistical test and independent-sample t test with the help of SPSS version 29 for windows. The findings of this study reveal that the RADEC learning model effectively strengthens students' creative thinking skills. The steps of this model help foster innovative creative thinking in students' problem-solving. The implications of this study highlight the RADEC model as an effective framework for fostering creativity in education. It supports curriculum developers and educators in designing learning processes that nurture students' innovative and critical thinking skills, essential for 21st-century challenges. The model's adaptability to diverse learning styles ensures broader applicability across educational contexts, contributing to the development of problem-solving abilities needed in real-world scenarios.